Cardiac complications in patients resulting from Covid-19 (Research, Society and Development, 2022)
Introduction: The Coronavirus (CoV) is part of a group of RNA viruses responsible for causing respiratory diseases, whether in humans or animals. This pathology can develop in a milder, moderate or severe form, being represented by Severe Acute Respiratory Syndrome. Objective: To identify and describe the complications resulting from COVID-19. Methods: This is an integrative literature review carried out in LILACS and MEDLINE, through the DeCS: Cardiopathies and Coronavirus, available in full in the last three years, excluding repeated articles in the databases. Results: 7 articles were selected that portrayed that the main complications of the coronavirus are cardiac, which can even worsen the outcome in patients with heart disease and in pregnant women. Final Considerations: In view of the above, we can see that cardiac complications were the most frequent and those that had a poor predictor of the outcome, since in most cases patients evolved to death by the combo cardiac complication + coronavirus.